2018
DOI: 10.1002/slct.201702478
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Emitting Magnetic Nanocomposites Assembled from Ag‐Decorated Fe3O4@SiO2 and Y2O3:Eu3+: Impact of Iron‐Oxide/Silver Nanoparticles on Eu3+ Emission

Abstract: The new multistep approach for co-assembling magnetic iron oxide nanoflowers with red-emitting Y 2 O 3 :Eu 3 + to form luminescent and magnetic nanocomposites was reported. The Fe 3 O 4 core prepared by solvothermal method was layered by SiO 2 shell and decorated with small size spherical Ag nanoparticles as well as further coated with Y 2 O 3 :Eu 3 + luminophore. The nanoflower shape Fe 3 O 4 core of size~110 nm and crystalline cubic structure of bifunctional iron-oxide@Y 2 O + (1 mol%) nanomaterials were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
1
7
0
1
Order By: Relevance
“…Emission spectra excited at different energies in the VUV and UV range (Figure ) exhibited, for the Eu‐doped materials, the characteristic emission lines from 5 D 0 → 7 F J (580–750 nm) and with lower intensity 5 D 2,1 → 7 F J (450–580 nm) transitions of Eu 3+ in Y 2 O 3 . The emission spectra were very similar to other Y 2 O 3 :Eu 3+ materials described in the published literature and indicated that, independently of the synthesis method, Eu 3+ ions occupied the same microsymmetry. Excitation energy above and below the band gap did not interfere with the emission profile, indicating that the Eu 3+ ions occupying C 2 and S 6 sites were excited from the same decay channels.…”
Section: Resultssupporting
confidence: 79%
“…Emission spectra excited at different energies in the VUV and UV range (Figure ) exhibited, for the Eu‐doped materials, the characteristic emission lines from 5 D 0 → 7 F J (580–750 nm) and with lower intensity 5 D 2,1 → 7 F J (450–580 nm) transitions of Eu 3+ in Y 2 O 3 . The emission spectra were very similar to other Y 2 O 3 :Eu 3+ materials described in the published literature and indicated that, independently of the synthesis method, Eu 3+ ions occupied the same microsymmetry. Excitation energy above and below the band gap did not interfere with the emission profile, indicating that the Eu 3+ ions occupying C 2 and S 6 sites were excited from the same decay channels.…”
Section: Resultssupporting
confidence: 79%
“…Thus, when Fe 3 O 4 is incorporated with CaTiO 3 :Ho,Yb, most of the excited-state energy is being utilized by the spin−spin domain of the paramagnetic nanoparticles, thus quenches the photoluminescence intensity. 38,39 Figure 6b depicts the CIE The ET between Ho 3+ and Yb 3+ ions can also be understood by the mechanism as illustrated in the Figure 7. Upon NIR excitation (980 nm), Ho 3+ electron gets excited to 5 I 6 state through the ground-state absorption (GSA).…”
Section: Resultsmentioning
confidence: 99%
“…As Fe 3+ is a paramagnetic system (basically d configured) in which excited-state energy is utilized in a spin–spin domain of the MNPs. Thus, when Fe 3 O 4 is incorporated with CaTiO 3 :Ho,Yb, most of the excited-state energy is being utilized by the spin–spin domain of the paramagnetic nanoparticles, thus quenches the photoluminescence intensity. , Figure b depicts the CIE chromaticity diagram. The coordinates are (0.33, 0.43), (0.32, 0.66), and (0.34, 0.39) for 5, 10, and 15%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The fine structure and the relative intensities of these transitions can be used to probe the local environment of the Eu 3+ ion and give information on the point group symmetry of the Eu 3+ site in the compounds ,. The important characteristics of these 4 f intraconfigurational transitions can be described as: i ) 5 D 0 → 7 F 1 is magnetic dipole transition, which intensity is largely independent of the chemical environment; ii ) 5 D 0 → 7 F 2 is electric dipole hypersensitive transition, which intensity is very strongly dependent on chemical environment and by far mostly influenced by small angular changes in the local coordination geometry,; iii ) 5 D 0 → 7 F 4 is electric dipole transition, which intensity is also dependent on chemical environment, but not hypersensitive and by far the most sensitive to lanthanide‐ligating atom bond distances and, therefore, to covalency.…”
Section: Methodsmentioning
confidence: 99%